2011
DOI: 10.3892/ijmm.2011.799
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase phosphatase-1 expression in macrophages is controlled by lymphocytes during macrophage activation

Abstract: Abstract. The viewpoints on the control of innate immune cells by the adaptive immune system during sepsis remain controversial. Mitogen-activated protein kinase phosphatase-1 (MKP-1) is essential to the negative control of innate immunity and suppresses the activation of macrophages by inhibiting activated mitogen-activated protein kinase (MAPK). The purpose of the current study was to observe inflammatory response and macrophage activation in mice with severe combined immunodeficiency (SCID) with endotoxemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The evidence for IL-10 as a M2 marker centers around the larger production of IL-10 from M-CSF cultured macrophages (M2-like) following stimulation with LPS compared to GM-CSF cultured macrophages (M1-like) (46). However, in the absence of exogenously added M-CSF or GM-CSF, other macrophage in vitro systems, RAW264.7 cell line (103) and thioglycollate-elicited peritoneal macrophages (104), also produced IL-10 in response to LPS stimulation. As IL-10 may diminish cytokine expression, this cytokine may play a role in buffering pro-inflammatory responses in the context of M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for IL-10 as a M2 marker centers around the larger production of IL-10 from M-CSF cultured macrophages (M2-like) following stimulation with LPS compared to GM-CSF cultured macrophages (M1-like) (46). However, in the absence of exogenously added M-CSF or GM-CSF, other macrophage in vitro systems, RAW264.7 cell line (103) and thioglycollate-elicited peritoneal macrophages (104), also produced IL-10 in response to LPS stimulation. As IL-10 may diminish cytokine expression, this cytokine may play a role in buffering pro-inflammatory responses in the context of M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…In a model of severe combined immunodeficiency with endotoxemia in mice Luo et al found decreased MKP-1 and increased TNF-α mRNA expression in peritoneal macrophages derived from SCID mice in comparison with cells from wild-type littermates prior to and following treatment with LPS [70]. Interestingly, when thioglycollate-treated macrophages were co-cultured with pan-T-cells, the expression of MKP-1 mRNA and protein increased and the expression levels of TNF-α and IL-6 were reduced as compared with wild-type macrophages.…”
Section: Physiological and Pathophysiological Roles Of Mkp-1mentioning
confidence: 99%